Dismissal protection and worker flows in OECD countries: Evidence from cross-country/cross-industry data - Andrea Bassanini; Andrea Garnero (Institute for the Study of Labor (IZA), 2012)
Exploiting a unique dataset including cross-country comparable hiring and separation rates by type of transition for 24 OECD countries, 23 business-sector industries and 13 years, we study the effect of dismissal regulations on different types of gross worker flows, defined as one-year transitions. We use both a difference-in-difference approach - in which the impact of regulations is identified by exploiting likely cross-industry differences in their impact - and standard time-series analysis - in which the effect of regulations is identified through regulatory changes over time. We find that the more restrictive the regulation, the smaller is the rate of within-industry job-to-job transitions, in particular towards permanent jobs. By contrast, we find no significant effect as regards separations involving an industry change or persistent joblessness. The extent of reinstatement in the case of unfair dismissal appears to be the most important regulatory determinant of gross worker flows. We also present a large battery of robustness checks that suggest that our findings are robust.
urn:nbn:de:101:1-201208174790
Keywords: J23; J24; J62; J63; 330; gross worker flows; resource reallocation; industry-specific human capital; job-to-job transitions; employment protection legislation; unfair dismissals; reinstatement; cross-country data; Kündigungsschutz; Arbeitsmobilität; Arbeitsplatzwechsel; Branche; Humankapital; Schätzung; OECD-Staaten